2021
DOI: 10.1186/s12301-020-00115-9
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of mini-percutaneous nephrolithotomy as daycare procedure: a prospective observational study

Abstract: Background To evaluate the safety, feasibility of mini-percutaneous nephrolithotomy (mPCNL) being carried out as a daycare surgery and to study the re-admission, stone clearance rate and complication rates following mPCNL. We also sought to find out the rate of requirement of ancillary procedure, after mPCNL. Methods In this prospective observational study, easily accessible patients above 18 years of age with renal and/or upper ureteric calculi, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
3
1
Order By: Relevance
“…The mean hospital stay in the study conducted by Rehman et al was 4.3 + 2.2 days which shows longer hospital stay than our study 21 . In Arthy et al the mean hospital stay was 17.25 + 11.23 hours which is shorter than our study [22]. It was similar to hospital stay in study by Brodie et al which was 2.24 days 23 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The mean hospital stay in the study conducted by Rehman et al was 4.3 + 2.2 days which shows longer hospital stay than our study 21 . In Arthy et al the mean hospital stay was 17.25 + 11.23 hours which is shorter than our study [22]. It was similar to hospital stay in study by Brodie et al which was 2.24 days 23 .…”
Section: Discussionsupporting
confidence: 81%
“…Our overall complication rate is similar to Baydilli et al which is 12.9 % 14 and much better than Ansari et al which is 49.1 % 17 . Arthy et al showed a complication rate of 8.7 %, lesser than our study including urosepsis in 2.9 % and hematuria in 5.7 % of the patients which did not require any blood transfusion 22 . This reduce rate of complication may be due to their small sample size (70) in comparison to our study (213).…”
Section: Discussioncontrasting
confidence: 75%
“…In institutes performing PCNL as day-care procedures, post-operative pain score remains an integral part of the discharge criteria [ 17 ]. Our study reports lower pain scores in supine than prone PCNL.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperatively, patients selected for day-care surgery were retained in the day-care area for 4 to 6 hours. They were encouraged to mobilize early and commence fluid intake (16). Postoperative analgesia was initiated in the recovery room, as effective pain management is crucial for the success of day-care surgeries.…”
Section: Methodsmentioning
confidence: 99%